Chemical composition and nematicidal activity of essential oils and their major compounds against Meloidogyne graminicola (Rice Root-Knot Nematode). Issue 6 (1st November 2020) - Ajith, M; Pankaj; Shakil, Najam Akthar; Kaushik, Prashant; Rana, Virendra Singh
ABSTRACT: Essential oils from Syzygium aromaticum, Cymbopogon flexuosus and Cymbopogon martinii were isolated by hydrodistillation method and analysed by GC-FID and GC-MS. Eugenol (87.1%) and citral (69.4%), respectively were identified as major compounds in clove and lemongrass oils while geraniol (81.6%) and geranyl acetate (12.4%) in palmarosa oil. Essential oils were evaluated for nematicidal activity against J2s of Meloidogyne graminicola . Results showed the mortality of J2s in clove and lemongrass oils ranged from 70.00-92.50% to 77.50-97.50% and 63.75-92.50% to 72.5-97.50% and that of palmarosa oil showed 70.00-95.00% to 73.75-98.75% mortality at 31.12 to 500 ppm after 24 and 96 hours. Geraniol, citral (sum of neral and geranial) and eugenol were also evaluated for their nematicidal activity. Results showed that geraniol (75.00-95.00% to 78.75-98.75%) possessed highest mortality followed by citral (67.5-93.75% to 72.50-97.50%) and eugenol (66.25-93.75% to 73.75-98.75%) at 31.12 to 500 ppm. Efficacy of the oils and compounds were comparable with carbofuran at 62.5ppm (76.0-87.67%) and 31.25ppm (70.67-83.33%) after 24-96 hours. Results showed that palmarosa oil possessed highest mortality followed by lemongrass and clove oils due to the presence of their major compounds.